The distance between two points (x1, y1) and ( x2, y2) is given as D = sqrt[(x2 - x1)^2 + ( y2 - y1)^2]

Substituting the values we have of the coordinates of the two points we get:

D = sqrt[(3a - a)^2 + ( -5 - 2)^2]

=> D...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

The distance between two points (x1, y1) and ( x2, y2) is given as D = sqrt[(x2 - x1)^2 + ( y2 - y1)^2]

Substituting the values we have of the coordinates of the two points we get:

D = sqrt[(3a - a)^2 + ( -5 - 2)^2]

=> D = sqrt [( 2a)^2 + 7^2]

=> D = sqrt (4a^2 + 49)

**The required distance between the points is sqrt (4a^2 + 49).**

Given the point (a,2) and the point (3a,-5).

We need to find the distance in terms of a.

We will use the distance between two points formula to calculate.

==> We know that :

D = sqrt[ (x1-x2)^2 + (y1-y2)^2 ]

==> D = sqrt( a-3a)^2 + (2+5)^2]

==> D = sqrt(4a^2 + 49)

**Then the distance between the points in terms of a is :**

**D = sqrt(4a^2+49)**